Identificación de nematodos fitoparásitos asociados al cultivo de café (Coffea arabica L.) en la provincia de Loja. - Gómez Guayllas, Erika Tatiana (2019)
Parasitic nematoda cause up to 12% loss in the agricultural production worldwide. The unnoticeable presence and attack of nematoda, together with other factors, considerably reduce the coffee farming degree of success, affecting the money income of families. This is the reason why this research was set out with the objective to assess the rate of impact and severity on roots, identify, characterize, and quantify the main genres of parasitic nematoda which affect the coffee production in Chaguarpamba, Quilanga, Olmedo, Loja, and Puyango cantons, that belong to Loja province at three different altitudinal grounds: high, medium, and low. In order to evaluate incidence and severity Taylor and Sasser scale was applied to all kind of nematoda. With relation to the identification and characterization, taxonomic keys were used. Finally, the extraction of nematoda was done through the Baerman tunnel method on floor, and the Stemerding method on roots. The samples were processed at the Loja Nematology Laboratory of the District Direction of Agroquality. The highest rates of impact and severity were observed at Olmedo canton, specifically on the low altitudinal ground, with a 66 % average in the case of incidence, and 66.4 % of severity. In relation with the identification of floor samples, ten genres of parasitic nematoda were found: Aphelenchus sp., Xiphynema sp., Helicotylenchus sp., Tylenchus sp., Pratylenchus sp., Tylenchulus sp., Psilenchus sp., Meloidogyne sp., Aphelenchoides sp., and Criconemoides sp; whose representative populations are: Helicotylenchus sp. (360 individals/100 cc of groud), Pratylenchus sp. (203 individuals/100 cc of ground), and Xiphynema sp. (156 individuals/100 cc of gound). On the other hand, only four genres were found in roots: Xiphynema pp., Helicotylenchus sp., Tylenchus sp., and Pratylenchus sp.; from these the last one has more population (127 individuals/100 g of roots). Finally, after establishing the correlation of each edaphic factor with the population of nematoda on ground, a relationship was found only between the sand and the nematoda population. Key words: NemAtoda, parasitic, identification, coffee.